Comparative Analysis of Memory and Alertness in the Perioperative Period of Operative Delivery in Pregnant Women With Preeclampsia and Without it With Different Kinds of Anesthesia - A. V. Shchegolev; D. M. Shirokov; O. A. Chernykh; B. N. Bogomolov; A. I. Levshankov (Неотложная медицинская помощь)
Relevance. The article investigates the choice of anesthesia technique during a caesarean section, which would minimally affect such components of cognitive functions as memory and alertness.The aim of the study is to increase the safety of anesthetic care in women of reproductive age by choosing the method of anesthesia.Material and methods. Two groups of maternity patients were examined: with a normal pregnancy and preeclampsia. They were tested according to a specially designed examination, which included: MoCA test, Benton’s test, Wechsler’s test, self-assessment questionnaire, hospital scale of anxiety and depression before and after surgical delivery.Results. According to the test results, it was found that memory and alertness in pregnant women were initially reduced (compared to the norm), especially with concomitant preeclampsia. When comparing the test results before and after abdominal delivery, it was found that the deterioration of memory and alertness parameters occurs less after the use of neuraxial methods (spinal and epidural anesthesia) compared to patients who underwent general combined anesthesia.